Benefits of use, and tolerance of, medium-chain triglyceride medical food in the management of Japanese patients with Alzheimer’s disease: a prospective, open-label pilot study - Ohnuma T (Dove Medical Press, 2016)
Tohru Ohnuma, Aiko Toda, Ayako Kimoto, Yuto Takebayashi, Ryoko Higashiyama, Yuko Tagata, Masanobu Ito, Tsuneyoshi Ota, Nobuto Shibata, Heii Arai Department of Psychiatry, Juntendo University Alzheimer’s Disease Project, Faculty of Medicine, Juntendo University, Tokyo, Japan Objectives: This is the first clinical trial of this type in Japan, designed to analyze two important aspects of Alzheimer’s disease (AD) management using medium-chain triglycerides. Axona was administered for 3 months (40 g of powder containing 20 g of caprylic triglycerides). We used an indurating, four-step dose-titration method (from 10 to 40 g per day) for 7 days before the trial, and examined the tolerance and adverse effects of this intervention. We also investigated its effect on cognitive function in mild-to-moderate AD patients.Patients and methods: This was a clinical intervention in 22 Japanese patients with sporadic AD at a mild-to-moderate stage (ten females, 12 males), mean age (± standard deviation) 63.9 (±8.5) years, Mini-Mental State Examination (MMSE) score, 10–25, seven patients were ApoE4-positive. During Axona administration, we examined changes in cognitive function by obtaining MMSE and AD assessment-scale scores. Intolerance and serum ketone concentrations were also examined.Results: The tolerance of Axona was good, without severe gastrointestinal adverse effects. Axona did not improve cognitive function in our sample of AD patients, even in those patients without the ApoE4 allele. However, some ApoE4-negative patients with baseline MMSE score ≥14 showed improvement in their cognitive functions.Conclusion: The modified dose-titration method, starting with a low dose of Axona, decreased gastrointestinal adverse effects in Japanese patients. Axona might be effective for some relatively mildly affected patients with AD (with cognitive function MMSE score of ≥14 and lacking the ApoE4 allele). Keywords: Alzheimer’s disease, medium-chain triglycerides, ketone, cognitive function, apolipoprotein E epsilon 4